PRAGMATIC ASPECTS OF IDIOMS IN ENGLISH AND UZBEK LANGUAGES - Abduraximova Madina Mamasiddiq kizi (International Journal of Literature and Language Studies, 2026)
This study explores the pragmatic dimensions of idioms in English and Uzbek, focusing on how context, speaker intention, and cultural background shape their usage. Using a contrastive analysis framework, the research examines idioms from both languages to identify functional similarities and cultural divergences. The findings reveal that while both languages use idioms for politeness, emphasis, and emotional coloring, Uzbek idioms rely more heavily on kinship and agricultural contexts, whereas English idioms frequently draw from maritime, sports, and commercial history. Understanding these pragmatic nuances is essential for effective cross-cultural communication and translation.